The Concept of Life Purpose in the Qur’an Surah adz-Dzariyat Verse 56 and its Relevance to The Quarter Life Crisis - Akbar, Muhammad Aulia; Drajat, Amroeni (Al-Fikru: Jurnal Ilmiah, 2025)
The phenomenon of quarter life crisis is increasingly prevalent among young Muslims in the digital age, which is fraught with demands for success, career uncertainty, and social pressure, causing existential anxiety and identity confusion. This study aims to explain the meaning of life purpose contained in the Qur'an Surah adz-Dzariyat verse 56 and its relevance to this phenomenon. The research method used is qualitative with a thematic interpretation approach. Data was obtained through literature review covering classical tafsir texts such as Ibn Katsir and al-Qurthubi, as well as modern tafsir works such as those by Quraish Shihab. Additionally, this study utilizes references from developmental psychology and logotherapy theories to enrich the discussion. The results of the study indicate that the concept of worship in the Qur'an Surah adz-Dzariyat verse 56 has a broad meaning, encompassing all aspects of human life aimed at seeking Allah's pleasure. This verse provides existential guidance for the younger generation in finding a clear, stable, and meaningful direction in life, thereby serving as a spiritual solution to the quarter-life crisis. The implications of this study are the need to strengthen spiritual literacy and contextual da'wah to help the younger generation deal with identity crises from a more transcendental perspective.